Binder resin for nonwoven fabric

The binder resin addresses fiber separation in nonwoven fabrics by forming spherical shapes on the fiber surface, maintaining and enhancing smoothness despite abrasion, thus improving the durability and feel of absorbent articles.

JP7618471B2Active Publication Date: 2025-01-21KAO CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021043815
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-17
Publication Date
2025-01-21
Estimated Expiration
2041-03-17

AI Technical Summary

Technical Problem

Nonwoven fabrics used in absorbent articles suffer from fiber separation due to abrasion, leading to reduced smoothness and potential hangnails, which existing technologies do not adequately address.

Method used

A binder resin with specific tensile strength and elongation properties is applied to nonwoven fabrics, forming three-dimensional spherical shapes on the fiber surface to prevent peeling and enhance smoothness during abrasion.

Benefits of technology

The binder resin maintains and improves the smoothness of nonwoven fabrics even under abrasive conditions by preventing fiber peeling and enhancing the surface texture.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007618471000001
    Figure 0007618471000001
  • Figure 0007618471000002
    Figure 0007618471000002
Patent Text Reader

Abstract

To provide a binder resin for nonwoven fabric capable of achieving a nonwoven fabric improving the smoothness with the abrasion without reducing smoothness even when being subjected to large abrasion by treating a fiber surface constituting the nonwoven fabric.SOLUTION: When a binder resin for nonwoven fabric is formed into a rectangular film with the density 0.9 g / cm3, length 50 mm, width 10 mm and thickness 0.5 mm, the tensile strength under 25°C is 0.1 MPa or more and 2.5 MPa or less and the tensile elongation is 600% or more and 1000% or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a binder resin for nonwoven fabric. [Background technology]

[0002] Nonwoven fabrics are used as components of absorbent articles, etc. Technologies have been developed to impart various functions to nonwoven fabrics.

[0003] For example, Patent Document 1 describes a technique for binding various particles, such as superabsorbent particles used in absorbent products, to the surface of fibers via polyamines or a binder such as polyamines. Patent Document 2 describes a substrate having thermally adhesive fibers coated with a lubricating oil such as grease or silicone, and a nonwoven fabric having standing fibers fixed to the substrate and free fibers. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 8-500270 [Patent Document 2] JP 2016-065335 A Summary of the Invention [Problem to be solved by the invention]

[0005] When nonwoven fabrics are incorporated into absorbent articles and used as materials, etc., if they are subjected to abrasion such as rubbing due to contact with clothing or skin, depending on the degree of abrasion, the fibers may peel off from the fused intersections. As a result, the peeled fibers may become frayed, reducing the smoothness of the nonwoven fabric. The above-mentioned patent documents do not disclose the problem of fraying of the fibers.

[0006] In view of the above, the present invention relates to a binder resin for nonwoven fabrics that can realize a nonwoven fabric whose smoothness does not decrease even when it is subjected to abrasion to a large extent, and whose smoothness can be improved as the fabric is subjected to abrasion, by treating the fiber surfaces that constitute the nonwoven fabric. [Means for solving the problem]

[0007] The present invention has a density of 0.9 g / cm 3 The present invention provides a binder resin for nonwoven fabrics, which, when formed into a rectangular film of length 50 mm, width 10 mm and thickness 0.5 mm, has a tensile strength of 0.1 MPa or more and 2.5 MPa or less and a tensile elongation of 600% or more and 1000% or less at 25°C. Effect of the Invention

[0008] The binder resin for nonwoven fabric of the present invention can treat the fiber surfaces constituting the nonwoven fabric to realize a nonwoven fabric whose smoothness does not decrease even when abrasion is severe, and whose smoothness can improve with abrasion. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, preferred embodiments of the binder resin for nonwoven fabrics (hereinafter, simply referred to as "binder resin") of the present invention will be described.

[0010] In the present invention, the compounds and derivatives thereof (hereinafter, sometimes collectively referred to as compounds) are used to mean not only the compounds themselves, but also their salts and ions. In the present invention, (meth)acrylic means one or both of acrylic and methacrylic. In the present invention, when a substituent is not specified as being substituted or unsubstituted, this means that the group may have an appropriate substituent.

[0011] <Binder resin for nonwoven fabric> The binder resin for nonwoven fabric of the present invention has a density of 0.9 g / cm 3When made into a rectangular film 50 mm long, 10 mm wide and 0.5 mm thick, the tensile strength at 25°C is 0.1 MPa or more and 2.5 MPa or less, and the tensile elongation is 600% or more and 1000% or less.

[0012] (Method of measuring tensile strength and tensile elongation) The tensile strength and tensile elongation can be measured by the following method in accordance with JIS K 7127. Note that a tensile elongation of 100% means a state in which a rectangular film has been stretched to a length (100 mm) that is twice its initial length (50 mm). (1) Preparation of film test specimens The binder resin is left in an electric dryer at 90°C for 12 hours to remove volatiles such as solvents, and then placed between two stainless steel plates with a shim plate (thickness 0.5 mm) creating a space between them. The pressing temperature is 150°C and the pressing pressure is 100 kg / cm. 2 Press for 60 seconds to remove the binder resin film (density 0.9 g / cm 3 The film thus obtained is cut into a rectangular shape measuring 50 mm in length and 10 mm in width to obtain a test piece for measurement. (2) Tensile test Using a precision universal testing machine (Autograph AG-IS (trade name), manufactured by Shimadzu Corporation), the tensile strength and tensile elongation are measured at a gripping distance of 10 mm and a tensile speed of 10 mm / min.

[0013] The binder resin for nonwoven fabric of the present invention has high viscosity and elasticity due to the above-mentioned properties. As a result, when a nonwoven fabric having the binder resin for nonwoven fabric of the present invention attached to its fiber surface is rubbed, the frictional force caused by the rub deforms the binder resin for nonwoven fabric of the present invention into a three-dimensional spherical shape. That is, the above-mentioned spherical parts are generated on the surface of the constituent fibers of the nonwoven fabric. As a result, the smoothness of the nonwoven fabric is not reduced even when rubbed, and rather the smoothness can be improved as the rub increases. In conventional nonwoven fabrics, when the nonwoven fabric is rubbed, frictional forces are applied to the constituent fibers, which can cause the fibers to peel off and become frayed. In particular, when the constituent fibers are core-sheath type composite fibers, the sheath part can come off from the core part. In contrast, when the binder resin for nonwoven fabrics of the present invention is present on the surface of the constituent fibers, the above-mentioned three-dimensional spherical parts can be generated so as to cover the peeled parts, and the above-mentioned effect of improving smoothness can be achieved.

[0014] When the nonwoven fabric contains thermoplastic fibers and has fusion points between the fibers, the above-mentioned fiber peeling is likely to occur mainly at the fusion points where the stress of frictional force is likely to concentrate. The above-mentioned effect is enhanced by changing the binder resin for nonwoven fabric of the present invention into spherical portions on the fiber surface after the fibers are peeled from the fusion points, i.e., the peeled surface or the surface of the remaining fusion points after peeling.

[0015] As the nonwoven fabric having the above-mentioned fusion points between fibers, a thermal bonded nonwoven fabric having fusion points between fibers formed by the fusion property of thermoplastic fibers is preferable. Among them, a nonwoven fabric produced by the air-through method (hereinafter also referred to as an air-through nonwoven fabric) is preferable from the viewpoint of soft touch. That is, the binder resin for nonwoven fabric of the present invention is preferably for use in an air-through nonwoven fabric. The nonwoven fabric will be described later.

[0016] From the viewpoint of improving the smoothness of the nonwoven fabric caused by rubbing, the tensile strength of the binder resin for nonwoven fabric of the present invention is 0.1 MPa or more, preferably 0.5 MPa or more, and more preferably 0.7 MPa or more, and the tensile strength of the binder resin for nonwoven fabric of the present invention is 2.5 MPa or less, preferably 2.3 MPa or less, and more preferably 2.1 MPa or less.

[0017] From the viewpoint of improving the smoothness of the nonwoven fabric caused by rubbing, the tensile elongation of the binder resin for nonwoven fabric of the present invention is 600% or more, preferably 630% or more, and more preferably 650% or more, whereas the tensile elongation of the binder resin for nonwoven fabric of the present invention is 1000% or less, preferably 950% or less, and more preferably 900% or less.

[0018] The binder resin for nonwoven fabric of the present invention can have a lower tensile strength and a higher tensile elongation by increasing the viscosity. Therefore, the tensile strength and tensile elongation can be obtained by appropriately controlling the rubber elasticity of the binder resin for nonwoven fabric of the present invention. For example, they can be controlled by the component ratio of the binder resin for nonwoven fabric of the present invention, the type of raw material compound (monomer) used in the synthesis, the molecular weight of the resin, etc.

[0019] From the viewpoint of improving the smoothness of the nonwoven fabric caused by rubbing, the binder resin for nonwoven fabric of the present invention preferably has a specific glass transition point. Specifically, the glass transition point of the binder resin for nonwoven fabric of the present invention is preferably −42° C. or higher, more preferably −41° C. or higher, and even more preferably −40° C. or higher. From the same viewpoint, the glass transition point of the binder resin for nonwoven fabric of the present invention is preferably 35° C. or lower, more preferably 20° C. or lower, and even more preferably 15° C. or lower. As a result, the binder resin for nonwoven fabric of the present invention does not become glassy in a normal temperature environment (for example, 25° C.) in which nonwoven fabrics are used, and the rubber elasticity inherent to the binder resin can be suitably exhibited.

[0020] [Method for measuring the glass transition temperature of binder resin for nonwoven fabric] The glass transition point is determined from a DSC curve obtained by differential scanning calorimetry according to JIS K 7121. (a) Prepare 0.01 g of the sample obtained in (1) above (Method for measuring tensile strength and tensile elongation). (b) Using a differential scanning calorimeter "DSC7000X" (product name, manufactured by Hitachi High-Tech Science Corporation), the procedure described in JIS K 7121 is carried out to determine the glass transition temperature.

[0021] From the viewpoint of improving workability, the binder resin for nonwoven fabric of the present invention preferably has the property of being soluble, dispersible or emulsifiable in a solvent such as water.

[0022] The type (polymer type) of the binder resin for nonwoven fabric of the present invention is not particularly limited as long as it can realize the above-mentioned properties, and examples thereof include acrylic resin, acrylic resin, ester resin, vinyl acetate resin, styrene resin, vinyl acetate-ethylene resin, and styrene-butadiene rubber. From the viewpoint of more effectively improving the smoothness of the nonwoven fabric caused by rubbing, acrylic resins are preferred.

[0023] The term "acrylic resin" refers to a polymer that contains at least one of a (meth)acrylic acid compound component and a (meth)acrylic acid derivative compound component as a main component of the polymer. In the acrylic resin used in the present invention, the bonding form of the components is not particularly limited, and the acrylic resin may be a block polymer or a random polymer.

[0024] The term "(meth)acrylic acid compound" refers to (meth)acrylic acid and its salts. Examples of counter ions constituting the salts of (meth)acrylic acid include alkali metal ions such as sodium ions and potassium ions, and alkaline earth metal ions such as magnesium ions and calcium ions. The term "(meth)acrylic acid derivative compound" refers to a compound (monomer) that can be derived from a (meth)acrylic acid compound. Examples of the (meth)acrylic acid derivative compound include (meth)acrylic acid esters, (meth)acrylamides, and (meth)acrylonitrile.

[0025] The (meth)acrylic acid compound and the (meth)acrylic acid derivative compound may each be used alone or in combination of two or more kinds.

[0026] The (meth)acrylic acid derivative compound used in the present invention is preferably a (meth)acrylic acid ester or a (meth)acrylamide, and more preferably a (meth)acrylic acid ester. In the (meth)acrylamide, the two hydrogen atoms of the nitrogen atom constituting the amide bond may be replaced with any substituent such as an alkyl group. The alkyl group may be an unsubstituted alkyl group or an alkyl group having a substituent. Examples of the alkyl group having a substituent include an alkyl group having an amino group as a substituent, which may be substituted with any substituent such as an alkyl group, and an alkyl group having an acyl group as a substituent. Among these, unsubstituted (meth)acrylamides and alkyl(meth)acrylamides are preferred. Examples of the (meth)acrylic acid ester include (meth)acrylic acid alkyl esters, polyalkylene glycol (meth)acrylates, (meth)acrylic acid aryl esters, and (meth)acrylic acid heteroaryl esters, and (meth)acrylic acid alkyl esters or polyalkylene glycol (meth)acrylates are preferred. The alkyl group bonded to the oxygen atom constituting the ester bond of the (meth)acrylic acid alkyl ester may be an unsubstituted alkyl group or an alkyl group having a substituent. Examples of the alkyl group having a substituent include an alkyl group having an amino group as a substituent, which may be substituted with any substituent such as a hydroxyalkyl group or an alkyl group, and an alkyl group having a betaine structure. Examples of the betaine structure include a carboxybetaine structure such as a carboxyquaternary ammonium structure, and more preferably a carboxydialkylammonium structure.

[0027] The acrylic resin used in the present invention preferably has a component derived from at least one of (meth)acrylic acid and salts thereof, and (meth)acrylic acid esters, and more preferably has a component derived from at least one of acrylic acid and salts thereof, and acrylic acid esters.

[0028] The acrylic resin used in the present invention may contain components derived from compounds (monomers) other than (meth)acrylic acid compounds and derivatives of (meth)acrylic acid. Examples of such compounds include ethylene, propylene, isopropylene, vinyl acetate, vinyl chloride, styrene, vinylpyrrolidone, and urethane compounds (monomers having a urethane bond).

[0029] Specific examples of the acrylic resin used in the present invention include (acrylic acid / acrylamide) copolymers such as (acrylic acid / t-butylacrylamide) copolymers, (acrylic acid / acrylamide / alkyl acrylate) copolymers such as (acrylic acid / acrylamide / ethyl acrylate) copolymers, (alkylacrylamide / acrylic acid / alkylaminoalkylacrylamide / polyethylene glycol methacrylate) copolymers, alkyl acrylate polymers, alkyl methacrylate copolymers, (acrylic acid / alkyl acrylate) copolymers, (acrylic acid / alkyl methacrylate) copolymers, (methacrylic acid / alkyl acrylate) copolymers, (methacrylic acid / alkyl methacrylate) copolymers, (alkyl acrylate / acrylamide) copolymers such as (alkyl acrylate / t-butylacrylamide) copolymers and (alkyl acrylate / octylacrylamide) copolymers, and (acrylic acid / alkyl acrylate / t-butylacrylamide) copolymers. (alkyl ester / alkyl acrylamide) copolymer, (methacrylic acid / alkyl ester of acrylic acid / alkyl acrylamide) copolymer, (methacryloyloxyethyl carboxybetaine / alkyl ester of methacrylic acid) copolymer, (alkyl acrylamide / alkylaminoalkyl acrylamide / polyethylene glycol methacrylate) copolymer, (octylacrylamide / hydroxypropyl acrylate / butylaminoethyl methacrylate) copolymer, (alkyl acrylamide / alkyl ester of acrylic acid / alkylaminoalkyl acrylamide / polyethylene glycol methacrylate) copolymer, (alkyl ester of acrylic acid / diacetone acrylamide) copolymer, (styrene / acrylic acid) copolymer, (styrene / alkyl ester of acrylic acid) copolymer, (styrene / acrylamide) copolymer, urethane-acrylic copolymer (copolymer of urethane compound and acrylic acid compound or its derivative), (vinyl pyrrolidone / acrylic acid / methacrylic acid) copolymer, (vinyl pyrrolidone / alkyl ester of acrylic acid / methacrylic acid) copolymer,Examples of the resin include a resin composed of an (octylacrylamide / hydroxypropyl acrylate / butylaminoethyl methacrylate) copolymer, a (methacryloyloxyethyl carboxybetaine / alkyl methacrylate ester) copolymer, and a (acrylic acid / alkyl acrylate / ethylamine oxide methacrylate) copolymer.

[0030] <Binder coating material for nonwoven fabric> The binder resin for nonwoven fabric of the present invention can be used as a binder coating material for nonwoven fabric containing the binder resin. This binder coating material for nonwoven fabric may consist of only the binder resin for nonwoven fabric of the present invention, or may contain other components within the range that does not impair the above-mentioned properties. For example, the components of the nonwoven fabric binder coating material may include, in addition to the binder resin for nonwoven fabric of the present invention, other binder resins, solvents, dispersants, emulsifiers or solubilizers for mixing the binder resin for nonwoven fabric of the present invention in the solvent, etc. Examples of the solvent include water, alcohols such as ethanol, isopropanol, and propylene glycol, and glycol ethers such as propylene glycol monomethyl ether and butyl diglycol, and from the viewpoints of improving the working environment and preventing deterioration of the fibers, water is preferred. The content of the binder resin of the present invention in the binder coating material for nonwoven fabric of the present invention can be appropriately set within a range that does not impair the above-mentioned characteristics. In particular, from the viewpoint of improving smoothness, the content of the binder resin of the present invention is preferably 0.5 mass% or more, more preferably 1.0 mass% or more, and the upper limit is 100 mass%.

[0031] <Nonwoven fabric> As described above, the nonwoven fabric containing the binder resin for nonwoven fabric of the present invention preferably has the binder resin for nonwoven fabric of the present invention and thermoplastic fibers, and has fusion points between the fibers (fusion points at the intersections of the fibers).

[0032] The thermoplastic fiber may be any fiber that is commonly used as a material for nonwoven fabrics without any particular limitations. For example, it may be a fiber made of a single resin component or a composite fiber made of multiple resin components. The composite fiber may have, for example, a core-sheath structure or a side-by-side structure. When using composite fibers containing a low melting point component and a high melting point component as the thermoplastic fiber (for example, composite fibers having a sheath-core structure in which the sheath is a low melting point component and the core is a high melting point component), the temperature of the hot air blown onto the fiber web in the manufacturing process is preferably equal to or higher than the melting point of the low melting point component and lower than the melting point of the high melting point component. More preferably, the temperature is equal to or higher than the melting point of the low melting point component and 10°C lower than the melting point of the high melting point component, and even more preferably, the temperature is 5°C or higher than the melting point of the low melting point component and 20°C or lower than the melting point of the high melting point component. A specific example of a composite fiber having a sheath-core structure in which the sheath is a low melting point component and the core is a high melting point component is a composite fiber having a sheath-core structure in which the sheath is made of polyethylene resin (hereinafter also referred to as PE) and the core is made of polyethylene terephthalate resin (hereinafter also referred to as PET).

[0033] The fusion points between fibers are the contact points between intersecting fibers where the fibers are bonded together by the fusion of the thermoplastic resin component. The fusion points are formed by, for example, melting the surfaces of the thermoplastic fibers by heat treatment during the manufacturing process of the nonwoven fabric, and fusing the fibers together. As the nonwoven fabric according to the present invention, for example, a thermal bonded nonwoven fabric is used, and more specifically, an air-through nonwoven fabric is used.

[0034] In a nonwoven fabric containing the binder resin for nonwoven fabric of the present invention, the binder resin for nonwoven fabric of the present invention is attached to the surface of the constituent fibers. This includes the binder resin for nonwoven fabric of the present invention being attached to the surface of the fusion point between fibers containing thermally adhesive fibers. The binder resin for nonwoven fabric of the present invention present on the surface of the fusion point between fibers preferably covers the outer surface of the portion where the fibers cross and overlap each other.

[0035] The binder resin for nonwoven fabric of the present invention is a resin component different from the constituent fibers of the nonwoven fabric, and is fixed to the surface of the constituent fibers after the nonwoven fabric is made. The amount of the binder resin for nonwoven fabric of the present invention applied is 0.5 g / m from the viewpoint of improving the smoothness of the nonwoven fabric caused by rubbing. 2 More than 1.0 g / m is preferable. 2 More preferably, 1.5 g / m 2 From the same viewpoint, the coating amount of the binder resin for nonwoven fabric is preferably 10 g / m 2 Less than 5 g / m is preferable. 2 Less than 3 g / m is more preferable. 2 The following is even more preferred:

[0036] In a nonwoven fabric containing the binder resin for nonwoven fabric of the present invention, the content of the binder resin for nonwoven fabric of the present invention in the nonwoven fabric is preferably 2% by mass or more, more preferably 5% by mass or more, and even more preferably 7% by mass or more, based on the total mass of the nonwoven fabric, from the viewpoint of improving the smoothness of the nonwoven fabric due to rubbing. On the other hand, the content of the binder resin for nonwoven fabric of the present invention is preferably 35% by mass or less, more preferably 25% by mass or less, and even more preferably 15% by mass or less, based on the total mass of the nonwoven fabric, from the same viewpoint.

[0037] As a method for applying the binder resin for nonwoven fabric of the present invention to a nonwoven fabric, various methods commonly used for this type of article can be adopted. For example, the binder resin for nonwoven fabric of the present invention can be sprayed and applied to one side of the nonwoven fabric by a spray or the like, and can be fixed to the surface of the constituent fibers, particularly the surfaces of the fusion points of the fiber intersections containing thermoplastic fibers. As a result, in the nonwoven fabric of the present invention, the binder is uniformly attached over the entire planar area of ​​the nonwoven fabric. In this application step, it is preferable to use the binder resin for nonwoven fabric of the present invention in the form of the binder coating material for nonwoven fabric described above. After spraying, a drying treatment may be performed as necessary. The drying treatment can be performed, for example, under conditions of 80°C to 150°C and 0.1 minutes to 90 minutes. By carrying out the treatment including the above-mentioned coating step, the smoothness of the nonwoven fabric surface can be improved.

[0038] In addition, a nonwoven fabric containing the binder resin for nonwoven fabric of the present invention can be produced by carrying out the treatment including the above-mentioned coating step. In this case, the raw material nonwoven fabric to be coated can be any of various materials produced by various commonly used methods. Furthermore, the nonwoven fabric containing the binder resin for nonwoven fabrics of the present invention obtained as described above can be processed into a desired shape as necessary, and can be combined with other components as necessary to produce various articles, for example, absorbent articles.

[0039] <Absorbent articles> The nonwoven fabric containing the binder resin for nonwoven fabric of the present invention can be used for various applications, for example, for absorbent articles. The absorbent article typically has a top sheet arranged on the skin contact side, a back sheet arranged on the non-skin contact side, and an absorbent sandwiched between the top sheet and the back sheet. In such absorbent articles, the nonwoven fabric of the present invention can be suitably used as a top sheet of absorbent articles such as diapers, sanitary napkins, panty liners, and urine absorption pads. Furthermore, the nonwoven fabric of the present invention can also be used as a sheet of the gather part, an exterior sheet, or a sheet of the wing part of the absorbent article. The nonwoven fabric of the present invention can also be used as a component of an eye mask or a mask. EXAMPLES

[0040] The present invention will be described in more detail below based on examples, but the present invention is not limited thereto. In the examples, "parts" and "%" are all based on mass unless otherwise specified. In the following tables, "-" means that the item does not have a corresponding value, etc.

[0041] Example 1 (1) Preparation of raw nonwoven fabric A core-sheath thermoplastic fiber (polyethylene terephthalate (PET)) (core): polyethylene (PE) (sheath) = 6:4 (mass ratio), fineness 3.4 dtex, fiber length 51 mm) with an average fiber diameter of 15 μm was used, and the basis weight was 20 g / m 2The raw nonwoven fabric was produced by the air-through method. The size of the raw nonwoven fabric was 100 mm x 100 mm. (2) Preparation of binder coating solution A binder coating liquid was prepared by mixing 10% by mass of binder solution B1 (see Table 1) having a solid content of about 50% by mass with 90% by mass of deionized water. (3) Spraying the binder coating liquid Next, the binder coating liquid was applied to the raw nonwoven fabric by spraying from above so that the binder resin was evenly attached. Next, the raw nonwoven fabric to which the binder coating liquid was applied was dried for 5 minutes at 120°C using an electric dryer. The coating amount of the solid content of the binder solution was 2 g / m 2 This was measured based on the change in the mass of the nonwoven fabric before and after the binder coating solution B1 was applied and dried. In this manner, a nonwoven fabric sample of Example 1 (a nonwoven fabric sample having a binder resin adhered to a raw material nonwoven fabric) was obtained.

[0042] (Examples 2 to 4, Comparative Examples 1 to 7) Nonwoven fabric samples and nonwoven fabric samples after rubbing were prepared in the same manner as in Example 1 for Examples 2 to 4 and Comparative Examples 1 to 7, except that binder solutions B2 to B4 and BC1 to BC7 shown in Table 1 below were used instead of binder solution B1.

[0043] [Table 1]

[0044] B1: Boncoat AB-886 (product name, manufactured by DIC Corporation) B2: Boncoat R3360 (product name, manufactured by DIC Corporation) B3: Polysol AT-741 (product name, manufactured by Showa Denko K.K.) B4: Aron NW-400 (product name, manufactured by Toagosei Co., Ltd.) BC1: DICFINE AJ-1820 (product name, manufactured by DIC Corporation) BC2: Polysol AT-731 (product name, manufactured by Showa Denko K.K.) BC3: Aron NW-7060 (product name, manufactured by Toagosei Co., Ltd.) BC4: Polysol AG-100 (product name, manufactured by Showa Denko K.K.) BC5: Polysol AP-1770 (product name, manufactured by Showa Denko K.K.) BC6: Polysol AT-860 (product name, manufactured by Showa Denko K.K.) BC7: Polysol ATF-732 (product name, manufactured by Showa Denko K.K.)

[0045] The nonwoven fabric samples of each of the Examples and Comparative Examples were subjected to the following measurements and tests, the results of which are shown in Table 2 below.

[0046] 1. Measurement of tensile strength and tensile elongation The tensile strength and tensile elongation of the film prepared from the binder resin for nonwoven fabric were measured based on the above-mentioned (Method of measuring tensile strength and tensile elongation).

[0047] 2. Scraping test (1) A disk (diameter 70 mm, 350 g) covered with urethane foam (Malt Filter MF-30 (product name, thickness 5 mm, surface friction coefficient 0.508) manufactured by Inoac Corporation) was attached to a rotating shaft. The attachment position was 20 mm off from the center of the disk. (2) The same urethane foam as above was laid on the underside of the nonwoven fabric sample of each Example and Comparative Example, and fixed on a table. The disk was placed on the nonwoven fabric sample. At this time, the load applied to the nonwoven fabric sample was only the weight of the disk. (3) Under this condition, the rotating shaft was rotated to rotate the disk over the nonwoven fabric sample. The rotation was performed 15 times, with one set consisting of three rotations clockwise and three rotations counterclockwise. The rotation time was 18 seconds per set.

[0048] 3. Measurement of MMD (mean coefficient of friction variation) Using an automatic surface tester (KES-FB4-A-SE (product name), manufactured by Kato Tech Co., Ltd.), the mean coefficient of friction variation (MMD) of the nonwoven fabric surface of each nonwoven fabric sample before and after the above-mentioned abrasion test was measured. The surface to be measured was the surface to be subjected to the above-mentioned abrasion test. A test specimen of each nonwoven fabric sample before and after the above-mentioned abrasion test was attached to a smooth metal test table. The contact surface of the contactor was pressed against the test specimen with a force of 49 cN, and the test specimen was moved horizontally for 2 cm at a constant speed of 0.1 cm / sec. A uniaxial tension of 19.6 cN / cm was applied to the test specimen. The contactor was made of 20 pieces of piano wire with a diameter of 0.5 mm arranged and bent into a U-shape with a width of 10 mm, and the contact surface was pressed against the test specimen with a force of 49 cN using a weight. The measured value of the mean deviation of the friction coefficient is expressed as the MMD value. This measurement was performed on the nonwoven fabric sample in both the MD (machine direction during manufacturing, or the direction parallel to one piece of the test piece) and CD (direction perpendicular to the MD, cross direction), and the average value was calculated using the following formula (S1), which was used as the average deviation of the friction coefficient. Friction coefficient mean deviation = {(MMD MD 2 +MMD CD 2 ) / 2} 1 / 2 (S1) The average deviation of the friction coefficient indicates the degree of variation in friction, with a smaller value indicating a higher degree of smoothness when touched by hand. This method was used to calculate the mean deviation of the coefficient of friction, i.e., MMD (mean coefficient of friction variation), for each nonwoven fabric sample before and after abrasion.

[0049] [Table 2]

[0050] <Notes for Table 2> Binder resin content [mass%] = [mass of binder resin / (mass of binder resin + mass of raw nonwoven fabric)] x 100 Improvement rate (%) = 100 x smoothness value before rubbing / smoothness value after rubbing

[0051] As shown in Table 2, the nonwoven fabric samples containing the binders of Examples 1 to 4, which had a tensile strength of 0.1 MPa to 2.5 MPa and a tensile elongation of 600% to 1000%, had a high improvement rate in smoothness due to rubbing. This improvement rate was not possible with the nonwoven fabric samples of Comparative Examples 1 to 7, which did not contain the above-mentioned binders.

Claims

1. An air-through nonwoven fabric for absorbent articles, comprising thermoplastic fibers and fusion points between fibers containing the thermoplastic fibers, Density 0.9g / cm 3 The air-through nonwoven fabric for absorbent articles has a binder resin disposed at least on the surface of the fusion points, the binder resin having a tensile strength of 0.1 MPa or more and 2.5 MPa or less and a tensile elongation of 600% or more and 1000% or less at 25°C when the binder resin is formed into a rectangular film of 50 mm in length, 10 mm in width and 0.5 mm in thickness.

2. An air-through nonwoven fabric for absorbent articles as described in claim 1, wherein the glass transition point of the binder resin is not lower than -42°C and not higher than 35°C.

3. An air-through nonwoven fabric for absorbent articles as described in claim 1 or 2, wherein the binder resin is an acrylic resin having a component derived from at least one of (meth)acrylic acid and its salts, and (meth)acrylic acid esters.

4. The air-through nonwoven fabric for absorbent articles according to any one of claims 1 to 3, wherein the content of the binder resin in the air-through nonwoven fabric for absorbent articles is 2% by mass or more and 35% by mass or less.

5. An air-through nonwoven fabric for absorbent articles described in any one of claims 1 to 4, which is for use as a component in an absorbent article that comes into contact with clothing or skin.

6. An air-through nonwoven fabric for absorbent articles as described in any one of claims 1 to 5, which is used for at least one of the surface sheet, the gathered portion sheet, the outer sheet, and the wing portion sheet of an absorbent article.

7. An absorbent article comprising the air-through nonwoven fabric for absorbent articles according to any one of claims 1 to 6.

8. A method for producing the air-through nonwoven fabric for absorbent articles according to any one of claims 1 to 6, comprising a step of applying the binder resin to a raw material air-through nonwoven fabric to be applied.

9. A method for producing an absorbent article, comprising a step of processing the air-through nonwoven fabric for absorbent articles obtained by the method for producing the air-through nonwoven fabric for absorbent articles according to claim 8 into a desired shape and combining it with other members.

Citation Information

Patent Citations

  • Particle bonding to fibers

    JP1996500270A

  • Female member for hook-and-loop fastener and manufacture thereof

    JP1998304909A

  • Absorbent body and method for manufacturing it

    JP2003204993A

  • Non-woven fabric and manufacturing method thereof

    JP2016065335A

  • Nonwoven fabric for forming and skin material for automobile

    JP2016156120A